The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/ajim.22369
|View full text |Cite
|
Sign up to set email alerts
|

Cancer mortality among Brazilian dentists

Abstract: If confirmed, these results indicate the need for limiting occupational exposures among dentists in addition to establishing screening programs to achieve early detection of selected malignant tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Moreover, two other ecological studies investigated the association between professional practice in certain occupations and the risk of death from cancer. Koifman et al 61 found a higher probability of death from non-Hodgkin's lymphoma, breast cancer, colon rectum, lung, brain, and all malignant neoplasm, among dentists of all genders in the age range from 20 to 79 years compared to the general population. Santos et al 62 found higher mortality from oropharyngeal, hypopharyngeal, laryngeal, lung, and bladder cancer but lower mortality from all leukemias in male mechanics.…”
Section: Research On Occupational Exposure and Cancer In Brazilmentioning
confidence: 99%
“…Moreover, two other ecological studies investigated the association between professional practice in certain occupations and the risk of death from cancer. Koifman et al 61 found a higher probability of death from non-Hodgkin's lymphoma, breast cancer, colon rectum, lung, brain, and all malignant neoplasm, among dentists of all genders in the age range from 20 to 79 years compared to the general population. Santos et al 62 found higher mortality from oropharyngeal, hypopharyngeal, laryngeal, lung, and bladder cancer but lower mortality from all leukemias in male mechanics.…”
Section: Research On Occupational Exposure and Cancer In Brazilmentioning
confidence: 99%
“…Por meio de dois outros estudos ecológicos, foi investigada a associação entre o exercício profissional em determinadas ocupações e o risco de óbitos por câncer. Koifman et al 61 constataram probabilidade mais alta de óbitos por linfoma não Hodgkin, câncer de mama, cólon reto, pulmão, cérebro e por todas as neoplasias malignas entre cirurgiões-dentistas de ambos os sexos, na faixa etária de 20 a 79 anos, em relação à população geral. Santos et al 62 verificaram maior mortalidade por câncer de orofaringe, hipofaringe, laringe, pulmão e bexiga, porém menor mortalidade por todas as leucemias entre mecânicos homens.…”
Section: And ((Cancer) or (Neoplasms) Or (Hematologic Neoplasms) Or (...unclassified
“…Furthermore, ionizing radiation used in dentistry, chromium and beryllium in dental prosthesis and mercury have carcinogenic effects. It has been suggested that dentists are at risk of some malignancies like bladder, brain, intestine and lung cancer, leukemia and malignant lymphomas [4].…”
Section: Sirmentioning
confidence: 99%